Um cotidiano ritualizado : a temporalidade militar em perspectiva etnográfica - Souza, Alexandre Colli de (Universidade Federal de São Carlos, 2008)
This dissertation thinks the temporality between the military through an ethnographic perspective. The pioneering works of anthropologists with armed forces in Brazil sought the understanding of the military through ethnographic perspective and escaped the dominant perspective of this issue so far: the relationship between military and politics. That look "inside" showed other perspectives of military sociability as its own vision of the military as a distinct group from the rest of citizens, a group with a set of inherent and exclusive features as well as a cosmology in which the hierarchy operates as logical classifier of all relations. These works raised suggestions I try to explore here, especially regarding the military temporality and its intersection with anthropological discussion of rituals. Within the theoretical anthropology production, ritual studies are constituted as a polyphonic field, producing a series of debates and different conceptions among themselves but always associated with the classic oppositions that founded the anthropological thought (individual / society, empiricism / rationalism ). By relating these two fields, I initially observed a series of data that led to think that the military temporality is lived and thought in understanding scheme in which time and actions could not simply be classified by the dichotomy that opposes the ritual moments and a routine (as a time less prescribed). The observation of military news, manuals, regulations, and reports indicated that all times of military life were marked by a series of regulations, codes of conduct regarding the physical appearance, body postures, uniform, internal behavior and external to the barracks, as well as for a variety of situations in which a military can pass. The military also have a complex series of celebrations and regulatory events in which directions on etiquette, protocol and ceremonial give way to how things should occur. The idea that these two fields, the regulation of the common life and the standardization of events, could not be treated as opposing ideas that guided the search for sociability data between military that become palpable the observation of that specific temporality, not dichotomous, which until then was a suggestive note. These results are presented here. In the opening chapter we present the background that led to the problem of this research, presenting ethnographies with military and anthropological discussion of rituals, and even at the end of this chapter, beginning the description of my insertion in the field. In the second chapter we present an analysis of military celebrations and events and in the third, the set of prescriptions ordering the training and the daily conduct of life of the military in many ways. Finally, I retake to discussion of the rites in the light of military temporality and its continuity solution, that smooth the classic opposition between ritual and daily life.
Keywords: Antropologia; Estado; Ritual; Forças Armadas; Hierarquia; Anthropology; State; Armed Forces; Hierarchy; Ritual; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA